Smart Parking System using MQTT Communication Protocol and IBM Cloud - Ashhwath, C; Rohitram, V; Sumathi, G (Journal of physics. Conference series, 2021)
In today’s world, the vast majority of people in large cities rely on automobiles. As a result, automobile parking has become an important part of our daily life. As a result, with such a vast population and a fast-paced world, vehicle parking has become a major concern. Such issues cause stress and strain, which might result in accidents. To help them out in such situations, a “smart” approach for running multilevel parking systems efficiently. To automate the parking procedure by monitoring metrics such as distance and available parking spaces, NodeMCU and IBM Cloud are used. The distance is measured, and the information is sent to Node-RED over the MQTT protocol. The Node-RED dashboard allows the user to view availability from any location. If the distance is too great, the space is unoccupied. If the parking area is fully occupied, the owner or person in control of the parking lot is also notified. This is accomplished by combining IFTTT and Node-RED. Watson is a virtual assistant that helps consumers with a variety of questions.